Improving the design of peripheral IV therapy by employing product development approach and rapid prototyping technology - Wan Yusoff, Wan Ahmad Yusmawiza; Azrai, Muhammad; Mohamad, Ahlam Hadi (Trans Tech Publications Ltd, 2014)
The aims of this research is to improve the design of IV cannula stopper or also known as heparin cap by utilizing the application of product design and development approach and employing Fused Deposition Modeling (FDM) machine. For this reason, the user requirements to identified target specifications and concept generation were proposed and the IV cannula stopper prototypes were fabricated using Rapid Prototyping technology (RP). This research would give an improvement over existing standard of IV cannula. The generated design from this research will improve the handling of IV cannula as well as ensuring its safety during the operation of IV cannula.